Exploring partnerships between local communities and timber companies: an experiment using the role-playing games approach - Purnomo, H.; Guizol, P.; Mendoza, G.A. (2009)
Cooperation among stakeholders is widely accepted as an effective management strategy. This paper describes an experimentalstudy that explores this cooperation using role-playing games, which is formulated within a multiagent simulation framework. This framework enables participants to take active roles in mimicking the collaborative decision environment and the behaviors and attitudes of the different stakeholders. The paper examines a forest plantation company in South Sumatra, Indonesia, which has cooperated with local communities since 2000. The experimental pilot study described in this paper explored the role of communication in partnership relationships between the company and the local communities living within and around the surroundings of the company’s plantation. These partnerships were explored and analyzed using the gaming approach involving university students taking the role of forest stakeholders, from both the timber company and the local communities. Lessons learned fromthe game provided the rationale for the establishment of a communication institution called “Forum Sebahu Sejalan.” This formal forum was constituted after a facilitated ex-postinteraction between representatives from the timber company and local communities. Results and observations drawn from the interactions show the potentials of the RPG approach and the formal forum in crafting resilient partnerships among stakeholders.